Ictal Epileptic Headache with Idiopathic Epilepsy - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2012)
Neurologists at the University of Rome, Italy report a 37-year-old woman with drug-resistant generalized epilepsy and headache who had a sudden headache during a 24-h EEG that displayed epileptic activity.